STRENGTHENING VILLAGE AND VILLAGE GOVERNMENT TOWARDS SUSTAINABLE DEVELOPMENT IN THE FRAMEWORK OF INCREASING COMMUNITY WELFARE - Maolani, Dedeng Yusuf (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The enactment of Law Number 6 Year 2014 in the course of government in Indonesia requires the Head of Sub-District, Village Head, Village Head and village / urban village apparatus as leaders, who deal directly with village / urban village communities to work together in an integrated and integrated manner to guard and implementing Law Number 6 Year 2014 and other laws and regulations in order to realize prosperity. This research is a type of research library using secondary data. This research is conducted by using qualitative methods and is done through an inductive approach, namely an approach that departs from things specifically for conclusions or general matters. The results of this study indicate that the Village Government is the administration of government affairs and interests of the local community in the system of government of the Unitary State of the Republic of Indonesia. The Village Authority is the implementation of the Village Government, the application of Village Development, Village community development, and community empowerment. Village income comes from the village's original income, the allocation of the State Revenues and Expenditures, part of the results of regional taxes and retribution from the Regency / City, Village fund allocation from the Regency / City balance fund, assistance finance from Regency / City and Province APBD, grants and donations, as well as other legitimate village income. They are building positive relationships between the sub-district head and the village head and village head in welcoming fiscal to village decentralisation and empowerment strategies and building public trust as an effort to strengthen village governance in improving community welfare.